2011
DOI: 10.1017/s0954579411000381
|View full text |Cite
|
Sign up to set email alerts
|

Social encounters in daily life and 2-year changes in metabolic risk factors in young women

Abstract: Research shows that poor social ties increase risks of morbidity and mortality from cardiovascular disease (CVD). However, little is known about the nature of everyday social encounters that give rise to this association, or when in the course of development they begin to shape disease-relevant biological processes. In this study, 122 adolescent females recorded the qualities of their everyday social interactions using electronic diaries. At the same time we measured components of the metabolic syndrome, a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 87 publications
0
32
0
Order By: Relevance
“…Such an association is not always obtained as previous reports did not find a relationship with depressive symptoms or perceived stress (cross-sectionally). 10;12 Lower SES is consistently associated with higher levels of negative emotions in adults. 31 Our sample is unique in that the adolescents were from a low to middle class community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an association is not always obtained as previous reports did not find a relationship with depressive symptoms or perceived stress (cross-sectionally). 10;12 Lower SES is consistently associated with higher levels of negative emotions in adults. 31 Our sample is unique in that the adolescents were from a low to middle class community.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic risk was defined by standardizing and averaging the risk factors that constitute the metabolic syndrome. 12 The Dunedin Study reported that children who were socially isolated and rejected were at elevated cardiovascular risk as young adults, defined as having at least three of six cardiovascular risk factors (overweight, low HDL-C, high BP, high cholesterol, high glycosolated hemoglobin, low maximum oxygen consumption). 13 In the Cardiovascular Risk in Young Finns Study, depressive symptoms at age 12 predicted the metabolic syndrome defined by standard National Cholesterol Education Program guidelines among women, but not men, 20 years later.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study of adolescent females, negative social interactions in everyday life were associated with increasing metabolic risk over a 2-year follow-up period (Ross, Martin, Chen, & Miller, 2011). Relationships in childhood and adolescence appear to be predictive of physical health even decades later in life.…”
mentioning
confidence: 99%
“…Ross and colleagues (2011) discovered that female adolescents who reported more negative daily interactions also experienced increased metabolic risk across two years. A national study of U. S. adults found that participants more emotionally reactive to daily stressors were also more likely to report a chronic physical health condition ten years later (Piazza, Charles, Sliwinski, Mogle, & Almeida, 2013).…”
mentioning
confidence: 99%